2020
DOI: 10.1002/dev.21971
|View full text |Cite|
|
Sign up to set email alerts
|

Electrophysiological signatures of visual statistical learning in 3‐month‐old infants at familial and low risk for autism spectrum disorder

Abstract: Visual statistical learning (VSL) refers to the ability to extract associations and conditional probabilities within the visual environment. It may serve as a precursor to cognitive and social communication development. Quantifying VSL in infants at familial risk (FR) for Autism Spectrum Disorder (ASD) provides opportunities to understand how genetic predisposition can influence early learning processes which may, in turn, lay a foundation for cognitive and social communication delays. We examined electroencep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 53 publications
6
12
0
Order By: Relevance
“…Overall, our data provide the first behavioral evidence of atypical SL in infants at risk for BAP by virtue of having a parent who shows high autistic traits. This finding is in line with those showing SL impairment in ASD children (Jeste et al 2015;Scott-Van Zeeland et al 2010) and infant siblings of children with ASD (Marin et al 2020) and confirms the importance of using implicit measures to understand the functioning of SL processes in typical and atypical population. Indeed, in studies where the ability to discriminate between statistically structured and non-structured streams of stimuli was tested in a task requiring participants' explicit responses, ASD adults and children performed just like TD individuals (e.g.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Overall, our data provide the first behavioral evidence of atypical SL in infants at risk for BAP by virtue of having a parent who shows high autistic traits. This finding is in line with those showing SL impairment in ASD children (Jeste et al 2015;Scott-Van Zeeland et al 2010) and infant siblings of children with ASD (Marin et al 2020) and confirms the importance of using implicit measures to understand the functioning of SL processes in typical and atypical population. Indeed, in studies where the ability to discriminate between statistically structured and non-structured streams of stimuli was tested in a task requiring participants' explicit responses, ASD adults and children performed just like TD individuals (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…The presence of an SL impairment in ASD is further confirmed by a recent ERP study that has tested infants at familial risk to develop ASD by virtue of having a sibling with a diagnosis (Marin et al 2020 ). Using a visual SL task in which infants were presented with sequences of shapes, the authors reported an atypical neural activation in infant siblings of ASD children compared with TD infants.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Nevertheless, a few studies report that individuals with ASD are able to learn statistical relations in long sequences (at least with a duration of 108 s) (Haebig et al, 2017; Mayo & Eigsti, 2012; Roser et al, 2015), despite showing atypical neural responses to these relations (Jeste et al, 2015; Marin et al, 2020; Scott‐Van Zeeland et al, 2010). In fact, regularities can occur on different timescales, short (local) or long (global), constituting a local versus global distinction (Sanders & Poeppel, 2007).…”
Section: Introductionmentioning
confidence: 99%